Antifungal edible coatings containing Argentinian propolis extract and their application in raspberries. (October 2020) - Moreno, María Alejandra; Vallejo, Ana María; Ballester, Ana-Rosa; Zampini, Catiana; Isla, María Inés; López-Rubio, Amparo; Fabra, María José
Abstract: Edible coatings based on gelatin containing an ethanolic extract of Propolis (PEE) collected of hives from Monte region in Argentina were developed and applied to raspberries ( Rubus idaeus L.) with the aim of prolonging their shelf life. Initially, the antifungal activity of PEE was evaluated against the major fungal pathogens of fruit and vegetables. Then, two different strategies were followed to incorporate the PEE into gelatin-based films: i) by directly incorporating the PEE into the protein matrix and ii) by previously encapsulating the PEE within zein nanocapsules with the aim of controlling the release of the PPE and extending their efficiency with time. Dry films were evaluated in terms of their optical, morphological, mechanical and water barrier properties. Likewise, the antifungal activity of the films against P. digitatum, P. expansum, P. italicum, A. alternata, A. carbonarius and B. cinerea was also assessed. Finally, film-forming dispersions (FFD) were applied to cold-stored raspberries and the fungal decay was determined throughout cold storage at 5 °C. The incorporation of PEE affected the mechanical response of the films, giving rise to more flexible and deformable edible films, but also more colored films with lower transparency. The active films revealed a notable antifungal activity against the tested fungus, showing a greater inhibitory effect on P. digitatum and B. cinerea. Adding PEE enhanced the antifungal activity during cold storage in raspberries. Furthermore, this proof-of-concept study proved the efficiency of the encapsulation process to reduce the infection incidence in raspberries stored at refrigeration temperatures for a longer period of time. Graphical abstract: Image 1 Highlights: Active edible coatings based on proteins and propolis extract (PEE) were developed . The antifungal activity of PEE was evaluated against the major fungal pathogens of fruits . Incorporation of PEE affected the physicochemical properties of the gelatin based films . Active films showed remarkable antifungal properties . Encapsulation of PEE into zein capsules reduced the infection incidence in raspberries .